Phytoconstituents, antioxidant and inhibitory activity against α-amylase and α-glucosidase of Opuntia ficus-indica - Lamees Rabi; Mohammad Altamimi; Nidal Jaradat (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Hyperglycemia and oxidative stress are associated with type 2 diabe-tes mellitus. The aim of this study is to evaluate the antioxidant, anti α-amylase and α-glucosidase activities of Opuntia ficus-indica cladodes and fruit juice. Four extracts of Opuntia ficus-indica cladodes were used, while fruit juice was only freeze-dried. Phytochemicals were determined of each extract and each extract was in-vitro evaluated for free radical scavenging, α-amylase and α-glucosidase inhibitory activities. Opuntia ficus-indica cladodes methanol extract has the highest contentin flavo-noid, phenols and alkaloids and it also has the highest antioxidant capaci-ty with IC50 value 6.16±0.59 µg/ml; compared to Trolox’s IC50value 2.09±1.7µg/ml. For α-amylase inhibitory effect aqueous extract was the most potent with IC50 value 16.98±0.77µg/ml followed by acetone ex-tract with IC50 value 25.11±0.89µg/ml. All extracts showed inhibitory activity with different extent against α-glucosidase enzyme, the aqueous extract showed the most potent activity followed by acetone extract.